A Pathway to Fabricate Gallium Nitride Embedded 3D High‐Index‐Contrast Optical Structures. Issue 21 (15th August 2022) - ElAfandy, Rami T.; Mi, Chenziyi; Wang, Sizhen; Han, Jung
Abstract: Optical engineering of gallium nitride (GaN) semiconductor material has enabled novel applications and technologies. 3D optical engineering is challenging and mostly accomplished by surface‐level patterning with subtractive or additive means. In this work a pathway, based on epitaxial conductivity control in conjunction with ion implant and subsequent electrochemical etching, to generate complex embedded nanoporous (NP)‐GaN/GaN or air/GaN 3D optical structures is presented. A range of subsurface structures is demonstrated including in‐plane NP‐GaN stripes and curved patterns, air/GaN microchannels, and localized, embedded distributed Bragg reflectors (DBRs) as micromirrors. To further demonstrate the versatility of the technique, adjacent DBR micromirrors, of different thicknesses, embedded depths, and widths, are created in the same fabrication steps. Computer simulations are used to shed light on the limitations of feature sizes of the presented technique. The approach is a simple, scalable, and versatile approach for fabricating embedded 3D optical structures readily extendable beyond GaN semiconductors. Abstract : Formation of embedded high‐contrast 3D optical structures in gallium nitride (GaN) is extremely limited by current fabrication techniques. A novel pathway for forming 3D embedded nanoporous‐GaN/GaN and air/GaN nanostructures with complex geometries is presented. A range of subsurface structures including nanoporous curved patterns, air microchannels, and localized, embedded distributed Bragg reflector micromirrors are demonstrated. The approach is simple, scalable and versatile.